Cost-effectiveness of Corrective Fusion Surgeries for Adult Spinal Deformities: A Comparison by Operative Method. Issue 18 (15th September 2021) - Arima, Hideyuki; Hasegawa, Tomohiko; Yamato, Yu; Kato, Masashi; Yoshida, Go; Banno, Tomohiro; Oe, Shin; Mihara, Yuki; Ushirozako, Hiroki; Yamada, Tomohiro; Watanabe, Yuh; Ide, Koichiro; et al.
Abstract : Study Design: Retrospective cohort study. Objective: The aim of this study was to summarize the cost-effectiveness of surgical treatment for adult spinal deformity (ASD) according to the operative method over 2 years postoperatively. Summary of Background Data: Extensive corrective fusion surgery for ASD requires numerous expensive implants, greatly contributing toward the national medical expenses. Previous national studies reported high complication rates in spinal surgeries using instrumentation. However, the cost-effectiveness of such procedures has not been scrutinized. Methods: In total, 173 ASD patients (151 women; mean age 69.1 years) who underwent corrective fusion between 2010 and 2017 were included. Cost-effectiveness was evaluated according to the cost of obtaining 1 quality-adjusted life year (QALY). Patients were divided into three groups: the "corrective fusion surgery using multiple Grade 2 osteotomy" (Grade-2) group, three-column osteotomy group (three-column), and lateral lumbar interbody fusion (LLIF) group. Results: The average medical cost for the initial surgery was USD 72, 240, and that during the 2 years after the initial surgery was USD 76, 294. The medical expenses for the initial surgery and those over the 2 years were higher in the LLIF group. The cumulative improvement in QALY over the 2 years did not significantly differ among the groups (0.13, 0.15, and 0.18 in the Grade-2, three-column, and LLIF groups, respectively). Cost/QALY 2 years after the surgery was USD 509, 370, 518, 406, and 463, 798 in the Grade-2, three-column, and LLIF groups, respectively. Conclusion: We summarized the medical costs and cost-effectiveness of three different surgical methods for ASD in patients with different backgrounds over 2 years postoperatively. The medical expense for the initial surgery was highest in the LLIF group, and the cumulative improvement in QALY over the 2 years tended to be higher in the LLIF group, but the difference was not significant; the overall cost-effectiveness was lowest in the LLIF group. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textWe summarized the cost-effectiveness of surgical treatment for adult spinal deformity by operative method over 2 years post-surgery. Cost/quality-adjusted life year 2 years after surgery was USD 492, 276 on average (USD 509, 370 for the multiple Grade-2 osteotomy, USD 518, 406 for the three-column osteotomy, and USD 463, 798 for the lateral lumbar interbody fusion group).